LD

\(\frac{x^2+x+4}{2}+\frac{x^2+x+7}{3}=\frac{x^2+x+13}{5}+\frac{x^2+x+16}{6}\)

Giúp mình với!!!!!!!!

KN
13 tháng 2 2020 lúc 19:55

Đặt \(x^2+x+10=u\)

Phương trình trở thành: \(\frac{u-6}{2}+\frac{u-3}{3}=\frac{u+3}{5}+\frac{u+6}{6}\)

\(\Rightarrow\frac{u}{2}-3+\frac{u}{3}-1=\frac{u}{5}+\frac{3}{5}+\frac{u}{6}+1\)

\(\Rightarrow\frac{u}{2}+\frac{u}{3}-\frac{u}{5}-\frac{u}{6}=3+1+1+\frac{3}{5}\)

\(\Rightarrow u\left(\frac{1}{2}+\frac{1}{3}-\frac{1}{5}-\frac{1}{6}\right)=\frac{28}{5}\)

\(\Rightarrow u.\frac{7}{15}=\frac{28}{5}\Rightarrow u=12\)

Lúc đó \(x^2+x+10=12\)

\(x^2+x-2=0\)

Ta có \(\Delta=1^2+4.2=9,\sqrt{\Delta}=3\)

\(\Rightarrow\orbr{\begin{cases}x=\frac{-1+3}{2}=1\\x=\frac{-1-3}{2}=-2\end{cases}}\)

Bình luận (0)
 Khách vãng lai đã xóa